Performance Evaluation of a 2D Front Tracking Method - a Direct Numerical Simulation Method for Multiphase Flows - Vu, Van Truong (Old Journal, 2017)
This paper evaluates the performance of a direct numerical simulation (DNS) method called "front-tracking" for multiphase flows. The interface separating two fluids or two phases is represented by connected elements that move on a fixed rectangular grid used for solving the Navier-Stokes equations. The phase’s values of material properties are specified by an indicator function that is reconstructed from the interface point location. The interface points are updated by the velocities, which are interpolated from the velocities on the fixed grid. The method is evaluated through a thorough investigation of the performance using a variety of verification and validation test cases including advection of the interface, computations of the surface tension, and interplay of the viscous and interfacial tension terms. The method is then used to simulate the evolution of the Rayleigh-Taylor instability. Good agreement in comparison of the present method with the previous literature proved the accuracy and capability of the method.